Histopathological aspects of co-administration of dexamethasone and diclofenac sodium on male albino rats - Sharef, Abdalmuhaimn Y.; Hamdi, Bushra Ahmed; Alnajar, Zahra Abdulqader (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Treatment of an animal with dexamethasone will result in sinuses extension, fat accumulation in the liver, and enlargement of hepatocytes. Whereas, non-steroidal anti-inflammatory drugs (diclofenac sodium) administration may lead to degeneration and formation of wide areas in the form of sinusoidal. Hydropic degeneration possibly is seen in the tubular epithelial cells of the kidney tissue. This study aimed to assess the toxic and side effects of dexamethasone and diclofenac sodium on the liver and kidney in rats, whether used separately or together. Methods: A total of 40 male albino rats were divided into four groups of ten in each, including the control group. One set was treated with dexamethasone (1.6 mg/kg/day), the other was treated with diclofenac sodium (30 mg /kg/day), and the last was treated with both drugs together at the same dose without mixture. Both drugs were administered intramuscularly for 30 days. Sections from the liver and kidney were stained by Hematoxeline and Eosin, then examined under a microscope. Results: Histopathological variation in the liver and kidney tissue of the treated animals have revealed that each drug (dexamethasone, diclofenac sodium) showed a significant alteration. Strong changes (+ + +) were observed in kidney tissue include degeneration, inflammatory aggregation, fibrosis, and edema, whereas in liver showed central vein dilatation, necrosis, and kupffer cells hyperplasia. Treating with the two drugs together, less alteration (+) in the tissues was noticed. Conclusion: The effect of both used drugs (dexamethasone and diclofenac sodium) was observed on the liver and kidney tissues of the experimental animals (rats) regardless of being applied separately or the two together. A probable inhibition role of the two drugs on each other have been noticed that lead to call for more detail investigation on this matter in years to come.